The “grave of oblivion”: Remembering the English Civil War in Sir Thomas Fairfax’s Short Memorials (1699) - Claire Gheeraert-Graffeuille (XVII-XVIII)
Writing against oblivion was a matter of urgency for witnesses of the English Civil Wars who sought to vindicate their past actions and restore historical truth on the basis of their first-hand experience of the conflict. Despite the “Act of Oblivion” (1660) seditious memories did not disappear after the Restoration, and memoirs dealing with the “troubles” circulated clandestinely. This article looks at Sir Thomas Fairfax’s Short Memorials, in which the General of the New Model Army justifies his military conduct and decision not to vote the execution of Charles I (1649). Fairfax’s testimony abounds in silences and historical inaccuracies; yet, and possibly for this reason, it provides valuable insights into the mechanisms of remembrance and oblivion. This paper examines the manuscripts and printed edition of the Short Memorials (1699) to illustrate how memorial strategies differed between these versions of the text, and interpret the significance of these variations.